2022
DOI: 10.1002/cam4.4655
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and inequities in colorectal and cervical cancer screening and diagnosis in Washington State

Abstract: Introduction Studies have shown that cancer screenings dropped dramatically following the onset of the coronavirus diseases 2019 (COVID‐19) pandemic. In this study, we examined differences in rates of cervical and colorectal cancer (CRC) screening and diagnosis indicators before and during the first year of the COVID‐19 pandemic. Methodology We used retrospective data from a large healthcare system in Washington State. Targeted screening data included completed cancer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
0
13
0
4
Order By: Relevance
“…Studies from the US also showed increased inequalities consequent to the screening program interruption, with a larger impact in the decrease of screening uptake in rural areas and for beneficiaries of public insurance or those who are not insured at all. 31,32 Possible impact Many studies from Italy and other countries reported a delay in diagnoses for many cancer sites. 33 ,34 In some studies, a shift to more advanced stages and different initial therapeutic approaches have been observed for breast cancer and colorectal cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from the US also showed increased inequalities consequent to the screening program interruption, with a larger impact in the decrease of screening uptake in rural areas and for beneficiaries of public insurance or those who are not insured at all. 31,32 Possible impact Many studies from Italy and other countries reported a delay in diagnoses for many cancer sites. 33 ,34 In some studies, a shift to more advanced stages and different initial therapeutic approaches have been observed for breast cancer and colorectal cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from the US also showed increased inequalities consequent to the screening program interruption, with a larger impact in the decrease of screening uptake in rural areas and for beneficiaries of public insurance or those who are not insured at all. 31, 32…”
Section: Discussionmentioning
confidence: 99%
“…A significant drop in cancer screening computed tomography imaging in the United States (−49 to −81.7%) [ 32 , 37 ] and diagnostic radiology rates (−16%) was observed in Switzerland [ 17 ]. Reductions in cancer screening were reported for cervical cancer (−7.5 to −90%) in Canada, the United States, Brazil, France, Taiwan, Belgium, and 17 selected low- and middle-income countries (LMICs) [ 19 ▪ , 21 ▪ 23 ▪ , 30 ▪▪ , 33 , 35 ▪ , 36 , 38 – 40 , 43 , 46 ]. A significant drop in digestive endoscopies (−19 to −29%) was reported in Lithuania and France [ 17 , 39 ].…”
Section: Covid-19 and Cancer Screening Programmentioning
confidence: 99%
“…A significant drop in digestive endoscopies (−19 to −29%) was reported in Lithuania and France [ 17 , 39 ]. Reductions in colon cancer screening (−8.1 to −95%) were registered in Canada, the United States, France, Belgium, Qatar, and 17 selected LMICs [ 14 , 15 , 16 ▪ , 23 ▪ , 25 , 30 ▪▪ , 33 , 35 ▪ , 36 39 , 43 , 44 ]. LCS rates fell in Canada, the United States, Ireland, and 17 selected LMICs (−21 to −44.6%) [ 11 , 24 , 30 ▪▪ ].…”
Section: Covid-19 and Cancer Screening Programmentioning
confidence: 99%
See 1 more Smart Citation